PERENCANAAN ARSITEKTUR ENTERPRISE PERGURUAN TINGGI DENGAN PENDEKATAAN ENTERPRISE ARCHITECTURE PLANNING (EAP) (STUDI KASUS POLITEKNIK PIKSI GANESHA): M. Farid Rifai - Jurnal, Redaksi Tim (PETIR, 2019)
major at consumer service. Information system Growth and Information Technology will affect to competition that growing competitive, this condition goes into effect also in the world of education especially for college that managed by society (private sector), claim the party of organizer to develop and develop information system in helping actifity business, reach organization target and service for stake holder especially related to data, information, technology and application. This Development and information system development must in harmony with instruct organization strategy (enterprise), found such cases of information system management experiences of failure in achieving target (objective) this organization because utilization disagree with college purpose and direction (organization). Enterprise Architecture Planning (EAP) as method or frame of reference to develop an information architecture. EAP is an architecture planning methods that orientation at business need that consist of data architecture, application and technology and implementation planning from architecture that has been made to support business activity to attainment of organization mission. EAP explains data architecture, application and technology that required to support organization business. Much developments IS experience of failure because need development IS are made base certain need without planning beforehand. Politeknik Piksi Ganesha, as one of higher education organizer that managed by private sector have strong comitment for information system utilization to support its business activity until must plan architecture enterprise. Architecture enterprise that will be modeled at Politeknik Piksi Ganesha, consist of : Data Architecture, Application, Technology Architecture, Roadmap implementation plan.. Architecture enterprise modeling relate to processes that already commonly use in business higher education management in Politeknik Piksi Ganesha Bandung, where as discussion scope is limited at area Academic, area Administrations and Finance, area HRD and General.